2021
DOI: 10.1177/23328584211033576
|View full text |Cite
|
Sign up to set email alerts
|

COVID on Campus: Assessing the Impact of the Pandemic on Undocumented College Students

Abstract: This article examines the initial impact of the COVID-19 pandemic on undocumented college students. Deploying an ecological framework, we situate students’ experiences within their families, communities, and educational institutions. We draw on qualitative and quantitative survey responses from 1,067 undocumented students attending California 4-year universities. Qualitative findings show that immigration status exacerbated the negative economic effects of the pandemic, leading to severe financial strains that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The pandemic has had a disproportionately negative impact on students of color and students living in poverty (Naff et al, 2020), including higher hospitalization rates and exposure to COVID-19-related environmental stressors (Centers for Disease Control and Prevention, 2020). Additionally, undocumented students may experience particular stress during the pandemic because of its impact on their financial security (Enriquez et al, 2021). Only approximately 20% of low-income youth received the mental health support they needed in the year following Hurricane Katrina (Madrid et al, 2008), further emphasizing the need to prioritize this during and after the pandemic.…”
Section: Likely Mental Health Impacts Of Covid-19 On Pk–12 Studentsmentioning
confidence: 99%
“…The pandemic has had a disproportionately negative impact on students of color and students living in poverty (Naff et al, 2020), including higher hospitalization rates and exposure to COVID-19-related environmental stressors (Centers for Disease Control and Prevention, 2020). Additionally, undocumented students may experience particular stress during the pandemic because of its impact on their financial security (Enriquez et al, 2021). Only approximately 20% of low-income youth received the mental health support they needed in the year following Hurricane Katrina (Madrid et al, 2008), further emphasizing the need to prioritize this during and after the pandemic.…”
Section: Likely Mental Health Impacts Of Covid-19 On Pk–12 Studentsmentioning
confidence: 99%
“…The level of student engagement varied according to the level of education and other sociodemographic characteristics [40]. According to Barrot et al [49], the pandemic exposed the iniquities within the education system, risk of drop-outs [50] adversely affected undocumented students who could not access regular education due to socioeconomic issues [51]. Transformation of education would be effective only when the education system and the stakeholders synchronize with the realization of student needs [52].…”
Section: Adaptive Motivationmentioning
confidence: 99%
“…In addition to general stressors associated with being a college student, undocu/DACAmented college students report constant fear and feeling ostracized due to their immigration status (Gonzales et al, 2013). The psychological literature suggests that these negative life experiences worsen the mental health of undocu/DACAmented college students, including increases in anxiety distress (Cadenas & Nienhusser, 2021; Enriquez, Chavarria, et al, 2021; Suárez-Orozco & López Hernández, 2020; Suárez-Orozco, Teranishi, & Suárez-Orozco, 2015) and feelings of depression (Cadenas & Nienhusser, 2021; Enriquez, Rosales, et al, 2021; Suárez-Orozco & López Hernández, 2020). For example, Suárez-Orozco and López Hernández (2020) found that rates of self-reported anxiety between undocumented women college students were four times and undocumented men college students were seven times higher that of the norm population as measured by the Generalized Anxiety Disorder Screener–7 (GAD-7) in the moderate and severe ranges.…”
mentioning
confidence: 99%